Transient efficacy of buparvaquone against the US isolate of Theileria orientalis Ikeda genotype in sub-clinically infected cattle - Bastos, Reginaldo G.; Hassan, Amany; Onzere, Cynthia K.; Herndon, David R.; Villarino, Nicolas F.; Laughery, Jacob M.; Fry, Lindsay M. (Frontiers in Veterinary Science, 2024)
Theileria orientalis, an economically significant tick-borne hemoparasite, infects cattle globally. The T. orientalis Ikeda genotype, transmitted by Haemaphysalis longicornis ticks, is associated with clinical manifestations characterized by anemia, abortions, and mortality, although subclinical infections prevail. Despite the common occurrence of subclinical infections, therapeutic interventions targeting T. orientalis Ikeda in such cases are currently lacking, impeding effective parasite control measures. To address this critical knowledge gap, we assessed the efficacy of buparvaquone (BPQ) in eliminating the T. orientalis Ikeda, US isolate, in sub-clinically infected cattle. Twelve subclinically infected calves, identified by the presence of T. orientalis in peripheral blood alongside the absence of fever and anemia, were enrolled in the study. Six calves received two treatments of the BPQ label dose (2.5 mg/kg) at a 48-hour interval, while additional three calves received the drug at a dosage of 6 mg/kg following the same regimen. Three untreated calves served as controls. Endpoint and quantitative PCR analyses revealed that BPQ exerted a transient effect on T. orientalis parasitemia. Parasites remained undetectable in peripheral blood until weeks 4 and 11 post-treatment in animals administered 2.5 mg/kg and 6 mg/kg of BPQ, respectively. Intriguingly, following recrudescence, administering 6 mg/kg to animals previously treated with 2.5 mg/kg did not result in a reduction in parasite load. Pharmacokinetic analysis data suggested that escalating the dosage led to a less than proportional increase in serum concentrations of BPQ. Moreover, a significant yet reversible decrease (P<0.05) in blood urea nitrogen was observed in animals treated with the drug, irrespective of the dosage. Despite parasitemia relapse, animals treated with 6 mg/kg BPQ exhibited a noteworthy decrease (P<0.05) in IgG levels specific to the T. orientalis major piroplasm surface protein compared to controls and animals treated with 2.5 mg/kg of the drug. In conclusion, BPQ did not demonstrate efficacy in clearing subclinical T. orientalis Ikeda infection. Future investigations are warranted to explore innovative therapeutic modalities that, in synergy with vaccines and diagnostic assays, can facilitate the development of comprehensive programs aimed at controlling and eradicating this parasite.